Cost effectiveness of HMG-CoA reductase inhibitor (statin) treatment related to the risk of coronary heart disease and cost of drug treatment. Issue 3 (1st September 1999) - Pickin, D M; McCabe, C J; Ramsay, L E; Payne, N; Haq, I U; Yeo, W W; Jackson, P R
Abstract : OBJECTIVES: To estimate the cost effectiveness of statin treatment in preventing coronary heart disease (CHD) and to examine the effect of the CHD risk level targeted and the cost of statins on the cost effectiveness of treatment. DESIGN: Cohort life table method using data from outcome trials. MAIN OUTCOME MEASURES: The cost per life year gained for lifelong statin treatment at annual CHD event risks of 4.5% (secondary prevention) and 3.0%, 2.0%, and 1.5% (all primary prevention), with the cost of statins varied from £100 to £800 per year. RESULTS: The costs per life year gained according to annual CHD event risk were: for 4.5%, £5100; 3.0%, £8200; 2.0%, £10 700; and 1.5%, £12 500. Reducing the cost of statins increases cost effectiveness, and narrows the difference in cost effectiveness across the range of CHD event risks. CONCLUSIONS: At current prices statin treatment for secondary prevention, and for primary prevention at a CHD event risk 3.0% per year, is as cost effective as many treatments in wide use. Primary prevention at lower CHD event risks (< 3.0% per year) is less cost effective and unlikely to be affordable at current prices and levels of health service funding. As the cost of statins falls, primary prevention at lower risk levels becomes more cost effective. However, the large volume of treatment needed will remain a major problem.